Comment on "Gastrointestinal Complications in Critically Ill Patients With COVID-19": An Update. Issue 6 (December 2021) - El Moheb, Mohamad; Christensen, Mathias A.; Naar, Leon; Gaitanidis, Apostolos; Breen, Kerry; Alser, Osaid; Maurer, Lydia R.; Gartland, Rajshri M.; Hwabejire, John O.; Velmahos, George; Kaafarani, Haytham M. A.
Abstract : Supplemental Digital Content is available in the text